1983
DOI: 10.1073/pnas.80.14.4218
|View full text |Cite
|
Sign up to set email alerts
|

Structure and biological activity of v-raf, a unique oncogene transduced by a retrovirus.

Abstract: We have molecularly cloned a unique acutely transforming replication-defective mouse type C virus (3611-MSV) and characterized its acquired oncogene. The viral genome closely resembles Moloney (M) murine leukemia virus (MuLV), except for a substitution in M-MuLV in the middle of p30 and the middle of the polymerase gene (pol). Heteroduplex analysis revealed that 2.4 kilobases of M-MuLV DNA were replaced by 1.2 kilobases of cellular DNA. The junctions between viral and cellular sequences were determined by DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
248
0
3

Year Published

1986
1986
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 441 publications
(257 citation statements)
references
References 40 publications
2
248
0
3
Order By: Relevance
“…The plasmid which expresses mcl-1 antisense transcript was picked and checked by both restriction enzyme digestions and sequencing. Plasmid 3611-MSV that contains MSV LTR driven v-raf (Rapp et al, 1983) …”
Section: Cell Line and Plasmidsmentioning
confidence: 99%
“…The plasmid which expresses mcl-1 antisense transcript was picked and checked by both restriction enzyme digestions and sequencing. Plasmid 3611-MSV that contains MSV LTR driven v-raf (Rapp et al, 1983) …”
Section: Cell Line and Plasmidsmentioning
confidence: 99%
“…The v-mil oncogene identified in MH2 (Jansen et al, 1983a, b) is the avian ortholog of the mammalian v-raf oncogene Sutrave et al, 1984) that was independently defined as a single oncogenic determinant in murine retrovirus 3611-MSV (Rapp et al, 1983). The c-mil(raf) proto-oncogene encodes the serine/threonine-specific protein kinase c-Mil(Raf) that is an important part of a conserved signalling pathway transducing signals from the cell surface to the nucleus (Bister and Jansen, 1986;Wellbrock et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Signal transmission involves recruitment of a highly conserved protein kinase cascade consisting of the dual-specificity mitogen-activated protein kinase kinase (MEK) and its substrate, a serine/threonine specific mitogen-activated protein kinase (MAPK). Early work with an oncogenic version of Raf-1 (v-Raf) that was transduced as part of a retrovirus, 3611 MSV [1], demonstrated that constitutive expression of Raf-1 kinase also influenced differentiation processes (reviewed by Rapp et al [2]). Specifically, upon infection of newborn mice an altered fate was observed in erythroid, B/myeloid and epithelial lineages [3] and upon infection of progenitor cells in culture erythroid, adipocyte or neuronal differentiation was induced [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%